Selling forest environmental services : market-based mechanisms for conservation and development - Pagiola, Stefano; Bishop, Joshua; Landell-Mills, Natasha (Earthscan Publications, 2002)
The risks posed by forest destruction throughout the world are highly significant for all. Not only are forests a critical source of timber and non-timber forest products, but they provide environmental services that are the basis of life on Earth. However, only rarely do beneficiaries pay for the goods and services they experience, and there are servere consquences as a result for the poor and for the forests themselves.; It has proved difficult to translate the theory of market-based approaches into practice. Based on extensive research and case studies of biodiversity conservation, watershed protected and carbon sequestration, this book demonstrates how payment systems can be establised in practice, their effectiveness and their implications for the poor.